Ion-exchange Resin Catalyzed Esterification of Lactic Acid with Isopropanol: a Kinetic Study - Amrit Pal Toor; Mamta Sharma; Sakshi Thakur; Ravinder K. Wanchoo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2011)
The kinetic behavior of esterification of lactic acid with isopropanol over an acidic cation exchange resin, Amberlyst 15, was studied under isothermal condition. Isopropyl lactate synthesized in this reaction is an important pharmaceutical intermediate. The experiments were carried out in a stirred batch reactor in the temperature range of 323.15 to 353.15 K. The effect of various parameters such as temperature, molar ratio and catalyst loading was studied. Variation in parameters on rate of reaction demonstrated that the reaction was intrinsically controlled. Kinetic modeling was performed using Eley-Rideal model which acceptably fits the experimental data. The activation energy was found to be 22.007 kJ/mol and frequency factor was 0.036809 l2 g-1 mol-1 min-1 for forward reaction. The value of entropy for the forward reaction was found to be 182.317 J K-1 mol-1. © 2011 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)